Utah obstetricians' opinions of planned home birth and conflicting NICE/ACOG guidelines: A qualitative study. Issue 2 (17th February 2017) - Rainey, Emily; Simonsen, Sara; Stanford, Joseph; Shoaf, Kimberley; Baayd, Jami
Abstract: Background: The United Kingdom's National Institute for Health and Care Excellence (NICE) recently published recommendations that support planned home birth for low‐risk women. The American College of Obstetricians and Gynecologists (ACOG) remains wary of planned home birth, asserting that hospitals and birthing centers are the safest birth settings. Our objective was to examine opinions of obstetricians in Salt Lake City, Utah about home birth in the context of rising home birth rates and conflicting guidelines. Methods: Participants were recruited through online searches of Salt Lake City obstetricians and through snowball sampling. We conducted individual interviews exploring experiences with and attitudes toward planned home birth and the ACOG/NICE guidelines. Results: Fifteen obstetricians who varied according to years of experience, location of medical training, sex, and subspecialty (resident, OB/GYN, maternal‐fetal medicine specialist) were interviewed. Participants did not recommend home birth but supported a woman's right to choose her birth setting. Obstetrician opinions about planned home birth were shaped by misconceptions of home birth benefits, confusion surrounding the scope of care at home and among home birth providers, and negative transfer experiences. Participants were unfamiliar with the literature on planned home birth and/or viewed the evidence as unreliable. Support for ACOG guidelines was high, particularly in the context of the United States health care setting. Conclusion: Physician objectivity may be limited by biases against home birth, which stem from limited familiarity with published evidence, negative experiences with home‐to‐hospital transfers, and distrust of home birth providers in a health care system not designed to support home birth.